2020
DOI: 10.3390/s20030938
|View full text |Cite
|
Sign up to set email alerts
|

On the Achievable Capacity of MIMO-OFDM Systems in the CathLab Environment

Abstract: In the last years, the evolution of digital communications has been harnessed by medical applications. In that context, wireless communications are preferable over wired communications, as they facilitate the work of health technicians by reducing cabling on the stretchers. However, the use of wireless communications is challenging, especially when high data rates and low latencies are required. In those scenarios, multiple-input multiple-output (MIMO) techniques might have an important role, thanks to the hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 15 publications
0
12
0
Order By: Relevance
“…Let us consider Table 3, which shows the simulated the EVM values of the QDA considering a different number quantization bits and different constellations. From the analysis of those values, it can be noted that the prototype met the EVM value for 64-QAM constellations required for Wi-Fi applications 5 . Moreover, it can be observed that when M = 6 quantization bits are considered, the QDA can support even larger constellations.…”
Section: Evmmentioning
confidence: 91%
See 2 more Smart Citations
“…Let us consider Table 3, which shows the simulated the EVM values of the QDA considering a different number quantization bits and different constellations. From the analysis of those values, it can be noted that the prototype met the EVM value for 64-QAM constellations required for Wi-Fi applications 5 . Moreover, it can be observed that when M = 6 quantization bits are considered, the QDA can support even larger constellations.…”
Section: Evmmentioning
confidence: 91%
“…For instance, by combining a bandwidth of B = 80 MHz with 64-QAM constellations and a code rate 5/6, it is possible to achieve R = 360 Mbps [6]. Since the capacity gains provided by the use of MIMO in the Wi-Fi-based Cathlab applications might not be as high as expected by the theory due to correlations between MIMO antennas [5], an alternative to increase the data rates per SS might resort to the adoption of larger constellations (i.e., higher values of M ). However, this will increase even more the (already high) envelope fluctuations of the transmitted OFDM signals, as well as the sensitivity to hardware imperfections and nonlinear distortions, causing severe amplification issues.…”
Section: System Characterization a Cathlab Environmentmentioning
confidence: 99%
See 1 more Smart Citation
“…However, as the increasing of information rate and transmission range, an LED-based VLC system encounters heavy traffic because of the extremely finite modulation bandwidth of LEDs and the divergence of light (He et al 2016b). However, multiinput multi-output (MIMO) technology has been generally studied in (Alqahtani et al 2019;Deng et al 2012;Guerreiro et al 2020;Saraereh et al 2019)during previous few years and applied to various wireless OFDM systems as it can improve the reliability and capacity of the systems. But there are still major issues like channel correlation, hardware impairments and implementations, modulation and interference management which need to be address for future based wireless systems (Lu et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In a word, a modern radar is required to detect targets in the midst of high-power jamming. It is worth noticing that, recently, the orthogonal frequency division multiplexing (OFDM) technique has been introduced to the array signal processing [3][4][5], and the joint radar and communication system [6,7]. Considering the demands of the military, the ECCM technology of the OFDM radar is investigated in this paper.…”
Section: Introductionmentioning
confidence: 99%